Wireless Network Security: Susceptibilities, Extortion and kiosk - Amjad, Mohd (International Journal of Computer Sciences and Engineering, 2013)
Wireless networking brings a whole new meaning to network security risk analysis and mitigation. With readily available equipment, attacks on wireless networks are very easy. The wireless security mechanism is not same as in wired networks. Because there is no user controlling for each individual node, wireless environment, and more importantly, scarce energy resources. The wireless security mechanism is not same as in wired networks. Because there is no user-controlling for each individual node, wireless environment, and more importantly, scarce energy resources. This paper looks at the basic risks inherent in wireless networking security protects a wireless network by denying access to the network itself before a user is successfully authenticated. This paper proposed a new security model which addresses three important types of active attacks like Rushing attack, Black hole and Replay attack. By using 3-roundof well known AES algorithm we implement this model. Thus it is easy for the administrator to identify these attacks using WPA. Different types of attack there related information, different cryptographic strength and performance of the proposed model get analyzed in this system. One particularly important improvement over the WPA standards is the inclusion of the Advanced Encryption Standard (AES) which could be used in many rounds to protect the overall network from the external attacks.